Persistent Symptoms and Objectively Measured Balance Performance Among OEF/OIF Veterans With Remote Mild Traumatic Brain Injury. Issue 6 (November 2018) - Hebert, Jeffrey R.; Forster, Jeri E.; Stearns-Yoder, Kelly A.; Penzenik, Molly E.; Brenner, Lisa A.
Abstract : Objective: To investigate linear relationships between dizziness, fatigue, and depression and posttraumatic stress disorder (PTSD) and objectively measured balance performance in Veterans with remote mild traumatic brain injury (mTBI). Setting: Academic laboratory; Veterans Affairs Medical Center. Participants: Thirty Veterans (28 men) who served in Iraq/Afghanistan and whose most recent mTBI was sustained more than 6 months prior to enrollment. Design: Cross-sectional, observational trial. Main Measures: The Computerized Dynamic Posturography-Sensory Organization Test (CDP-SOT) and the Community Balance and Mobility (CB&M) scale measured balance. Dizziness (Dizziness Handicap Inventory), fatigue (Modified Fatigue Impact Scale), depression-related symptoms (Beck Depression Inventory-II), and PTSD-related symptoms (PTSD Checklist 5) were also measured. Results: Objectively measured balance, CDP-SOT composite, was impaired (mean score of 67.9). CDP-SOT scores correlated with dizziness ( r = −0.53; P = .002), fatigue ( r = −0.38; P = .03), depression ( r = −0.55; P = .001), and PTSD symptoms ( r = −0.53; P = .002). Dizziness, time since most recent mTBI, and PTSD symptoms and depression combined explained significant variability in CDP-SOT scores ( R 2 = 0.46; P = .003), as did fatigue depression and PTSD symptoms ( R 2 = 0.33; P = .01). Conclusions: Impaired balance was identified among the cohort. Findings suggest that dizziness, fatigue, depression and PTSD, and time since most recent mTBI may influence balance performance. Additional research is needed to identify the potentially interrelated natural histories of these co-occurring symptoms.